Global Leaders for Global Teams: Leaders with Multicultural Experiences Communicate and Lead More Effectively, Especially in Multinational Teams - Lu, Jackson G.; Swaab, Roderick I.; Galinsky, Adam D. (Organization Science, 2022)
In an era of globalization, it is commonly assumed that multicultural experiences foster leadership effectiveness. However, little research has systematically tested this assumption. We develop a theoretical perspective that articulates how and when multicultural experiences increase leadership effectiveness. We hypothesize that broad multicultural experiences increase individuals’ leadership effectiveness by developing their communication competence. Because communication competence is particularly important for leading teams that are more multinational, we further hypothesize that individuals with broader multicultural experiences are particularly effective when leading more versus less multinational teams. Four studies test our theory using mixed methods (field survey, archival panel, field experiments) and diverse populations (corporate managers, soccer managers, hackathon leaders) in different countries (Australia, Britain, China, America). In Study 1, corporate managers with broader multicultural experiences were rated as more effective leaders, an effect mediated by communication competence. Analyzing a 25-year archival panel of English Premier League soccer managers, Study 2 replicates the positive effect of broad multicultural experiences using a team performance measure of leadership effectiveness. Importantly, this effect was moderated by team national diversity: soccer managers with broader multicultural experiences were particularly effective when leading teams with greater national diversity. Study 3 (digital health hackathon) and Study 4 (COVID-19 policy hackathon) replicate these effects in two field experiments, in which individuals with varying levels of multicultural experiences were randomly assigned to lead hackathon teams that naturally varied in national diversity. Overall, our research suggests that broad multicultural experiences help leaders communicate more competently and lead more effectively, especially when leading multinational teams.